The capillary adhesion technique: a versatile method for determining the liquid adhesion force and sample stiffness - Gandyra, Daniel; Walheim, Stefan; Gorb, Stanislav; Barthlott, Wilhelm; Schimmel, Thomas (Beilstein Journal of Nanotechnology, 2015)
We report a novel, practical technique for the concerted, simultaneous determination of both the adhesion force of a small structure or structural unit (e.g., an individual filament, hair, micromechanical component or microsensor) to a liquid and its elastic properties. The method involves the creation and development of a liquid meniscus upon touching a liquid surface with the structure, and the subsequent disruption of this liquid meniscus upon removal. The evaluation of the meniscus shape immediately before snap-off of the meniscus allows the quantitative determination of the liquid adhesion force. Concurrently, by measuring and evaluating the deformation of the structure under investigation, its elastic properties can be determined. The sensitivity of the method is remarkably high, practically limited by the resolution of the camera capturing the process. Adhesion forces down to 10 µN and spring constants up to 2 N/m were measured. Three exemplary applications of this method are demonstrated: (1) determination of the water adhesion force and the elasticity of individual hairs (trichomes) of the floating fern Salvinia molesta. (2) The investigation of human head hairs both with and without functional surface coatings (a topic of high relevance in the field of hair cosmetics) was performed. The method also resulted in the measurement of an elastic modulus (Young’s modulus) for individual hairs of 3.0 × 105 N/cm2, which is within the typical range known for human hair. (3) Finally, the accuracy and validity of the capillary adhesion technique was proven by examining calibrated atomic force microscopy cantilevers, reproducing the spring constants calibrated using other methods.
Keywords: adhesion; AFM cantilever; air layer; capillary forces; hairs; measurement; micromechanical systems; microstructures; Salvinia effect; Salvinia molesta; sensors; stiffness; superhydrophobic surfaces